Respiratory Virology and Immunogenicity - Pokorski, Mieczyslaw (Advances in Experimental Medicine and Biology,, 2015)
This volume provides a modern look on the age-old influenza infection and the preventive role of anti-influenza shots. Influenza pandemic outbreaks are unrelenting despite the growing understanding of the molecular basis of viral infection and its spreads. A leap in medical technologies has revolutionized the design of new influenza vaccines. The chapters cover vaccination strategies in various age-groups of people and provide the extensive amount of knowledge on the immune response to influenza vaccination in a spectrum of disease conditions.